E-mail authentication what, why, how?. - Allman, Eric (New York ACM, 2006)
There are ways to know for sure that that e-mail really was sent by your bank, but which method is best?
Keywords: Information systems; Information systems applications; Communications applications; Electronic mail; Information storage and retrieval; Systems and software; Distributed systems; Computing Milieux; Computers and society; Social issues; Management of computing and information systems; Security and protection; Authentication; Security